2020
DOI: 10.1088/1361-665x/abca51
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid electrostatic and gecko-inspired gripping pads for manipulating bulky, non-smooth items

Abstract: We present hybrid electrostatic and gecko-inspired gripping pads that help robots to lift and carry bulky objects. The directional, gecko-inspired adhesive provides a controllable shear force with low normal force, providing a very high effective coefficient of friction so that items like bags full of groceries and heavy cardboard boxes can be lifted using only 1–2 N of squeezing force. The addition of electrostatics helps the pads to conform to non-smooth surfaces, providing substantially higher shear forces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Acrylic, brushed steel, and paper were chosen as common materials representative of low, medium, and high absolute rugosity, respectively. It has been shown that, rather than surface polarity or charge, this metric of roughness primarily determines the strength of the van der Waals forces due to its influence on achievable intimate contact area ( 36 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Acrylic, brushed steel, and paper were chosen as common materials representative of low, medium, and high absolute rugosity, respectively. It has been shown that, rather than surface polarity or charge, this metric of roughness primarily determines the strength of the van der Waals forces due to its influence on achievable intimate contact area ( 36 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present case we are also subject to molding limitations for the microscopic features. However, an option is to partially fill the wedges with a high dielectric material, for example, calcium copper titanate (CCTO), as employed in [31] for hybrid grippers.…”
Section: Discussionmentioning
confidence: 99%
“…In other work, researchers have integrated gecko-inspired adhesives with electrostatics to increase conformation and adhesion, especially on microrough surfaces. [28][29][30][31] Related work also includes efforts to increase the electrostatic pressure for a given voltage by using materials with a high permittivity. [31][32][33][34] This work is only partially relevant in the present case because an electrostatic pressure is used only for making initial contact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dedicated to communication at its early stages of development, it is now mainly used for soft robotic applications [ 3 , 4 , 5 , 6 ] thanks to its easy force control via applied voltage, and the capability to pick up fragile objects. Even if performances of different materials have been explored such as composite and elastomer [ 7 , 8 , 9 , 10 , 11 ], the principal materials used to design such electrostatic actuators are electrostrictive polymers, because they are light-weight, affordable, flexible, controllable to hold atypical shapes, and easily customized for different applications versus traditional grippers materials [ 12 , 13 , 14 ]. These polymers, despite their important strains and decent forces, need a high voltage excitation to reach sufficient mechanical deformation.…”
Section: Introductionmentioning
confidence: 99%